OPTIMIZATION AND CHARACTERIZATION OF QUERCETIN VITAMIN C NANO-PHYTOSOME FORMULATION - NANDAYASA, WIRA WAHYUDI; FEBRIYENTI; LUCIDA, HENNY (International Journal of Applied Pharmaceutics, 2023)
Objective: To design an optimal formulation for quercetin and vitamin C nano-phytosome. Methods: Nano-phytosomes are prepared by the thin layer hydration technique using a 2-level-5-factor design experimental. A total of 32 experimental formulas were used for data analysis. The ratio of quercetin: soy lecithin (X1), the ratio of quercetin: cholesterol (X2), stirring speed (X3), stirring temperature (X4), and stirring time (X5) were used as independent factors, while globule size as a dependent factor. Data analysis was carried out by Design Expert12® application. Characterization of the optimal formula included physicochemical evaluation, globule size analysis, zeta potential, polydispersity index, entrapment efficiency, Transition Electron Microscopy (TEM) analysis, and FTIR analysis. Results: The optimal formula consisted of quercetin: vitamin C: lecithin: cholesterol ratio of 1: 1: 1.046: 0.105 mol; stirring speed 763.986 rpm; stirring time of 59 min, at temperature 51.73 °C which produced 59.26 nm average globule size, PDI value 0.66; zeta potential value-35.93±0.95 mV and average SPAN value 0.61. This formulation showed entrapment efficiency of quercetin 91.69±0.18 % and vitamin C 90.82±0.13 %. The TEM and FITR analysis showed the morphological of the globules and interactions between the drugs, soy lecithin, and cholesterol to form nano-phytosomes. Conclusion: The conditions to obtain the optimal formula for quercetin vitamin C nano-phytosome consisted of quercetin: vitamin C: lecithin: cholesterol ratio of 1: 1: 1.046: 0.105 mol; stirring speed 763.986 rpm; stirring time of 59 min, and at temperature 51.73 °C